2022
DOI: 10.3892/mmr.2022.12639
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long non‑coding RNA DDX11‑AS1 inhibits the proliferation, migration and paclitaxel resistance of breast cancer cells by upregulating microRNA‑497 expression

Abstract: drug resistance is a major problem to overcome in the treatment of cancer; therefore, identifying therapeutic targets for drug resistance is a point of focus in the field of cancer research. long non-coding rnas (lncrnas) and micrornas (mirs) not only affect gene expression regulation during cell proliferation, but also have several potential roles in the drug resistance of malignant tumors. reverse transcription-quantitative Pcr was used to detect the expression levels of ddX11 antisense rna 1 (ddX11-aS1) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Another study revealed that lncRNA-NRON inhibited BC development via regulating the miR-302b/serine-and arginine-rich splicing factor 2 axis [25]. Other studies also demonstrated that DDX11-AS1 was upregulated in drug resistant BC cell lines, thus suggesting that it could be involved in chemotherapy resistance in BC [16,17]. Nonetheless, the biological signi cance of DDX11-AS1 in BC remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study revealed that lncRNA-NRON inhibited BC development via regulating the miR-302b/serine-and arginine-rich splicing factor 2 axis [25]. Other studies also demonstrated that DDX11-AS1 was upregulated in drug resistant BC cell lines, thus suggesting that it could be involved in chemotherapy resistance in BC [16,17]. Nonetheless, the biological signi cance of DDX11-AS1 in BC remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lncRNA DDX11-AS1, also known as cohesion regulator non-coding RNA, is involved in several types of cancer, including hepatocarcinoma, lung cancer, colorectal carcinoma, renal carcinoma and bladder cancer [13][14][15]. Another study also revealed that DDX11-AS1 was associated with the resistance of BC cells to chemotherapy [16,17]. Nevertheless, the detailed molecular mechanism underlying the effect of DDX11-AS1 on BC oncogenesis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…What's more, KLF3-AS1 can attenuate miR-185-5p-mediated inhibition of KLF3 to impair cell migration and invasion 38 . DDX11-AS1 plays a crucial role in proliferation, migration and resistance to chemotherapy of breast cancer cells by downregulating the expression of miR-497 39 .…”
Section: Discussionmentioning
confidence: 99%
“…MTT colorimetric assay was carried out following previous methods. 20,21 Cells (1000 cells/well) were plated in a 96-well plate, and each well was mixed with 20-μL MTT solution (5 mg/L; Sigma-Aldrich). After 4 h, the generated formazan crystals were dissolved in 150-μL dimethyl sulfoxide (DMSO; Sigma-Aldrich).…”
Section: Mtt Assaymentioning
confidence: 99%